Estrutura genética de populações de Rhizoctonia oryzae-sativae do arroz em São Paulo, Brasil, e em meta, Colômbia, e potencial adaptativo do patógeno à Urochloa spp - Pereira, Danilo Augusto dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The rice sheath-blight complex comprises three diseases caused by different Rhizoctonia species: sheath blight (caused by R. solani AG-1 IA), aggregated sheath spot (R. oryzae-sativae), and sheath spots (R. oryzae). To be able to distinguish among the causal agents is a critical step in order to manage them effectively. In a recent survey in five rice cropping areas from the Paraíba Valley region, Brazil, and from the Llanos in Colombia, R. oryzae-sativae (the aggregated sheath spot pathogen) was the predominant species on both countries. In this study, our primary objective was to determine the genetic structure of populations of R. oryzae-sativae from rice paddy fields sampled from the Paraiba Valley and the Colombian Llanos. We inferred about gene flow among populations within and between countries and the pathogen's main reproductive mode. The second objective was to infer the potential of the two brazilian populations of R. oryzae-sativae to adapt and become pathogen of forage pastures of the genus Urochloa. Once these forage species are intensively cropped in adjacent areas or under rotation with rice, they might be exerting strong selection pressure on R. oryzae-sativae populations. Population structure analyses were based on genotyping fungal isolates from four populations of the pathogen using five microsatellites markers. Gene flow was detected among geographically close and distant populations. Evidences of sexual reproduction and low clonal fraction found in the populations, indicated the predominance of a mixed reproductive system. It is plausible that basidiospores play a more important role on the disease cycle than previously thought. Isolates from the two brazilian populations of R. oryzae-sativae were pathogenic and varied on aggressiveness to Urochloa spp. However, low levels of heritability for aggressiveness were detected, indicating a yet limited adaptation to Urochloa spp

O complexo de manchas da bainha do arroz engloba três doenças causadas por diferentes espécies de Rhizoctonia: a queima-da-bainha (causada R. solani AG-1 IA), a mancha agregada da bainha (R. oryzae-sativae) e a mancha da bainha (R. oryzae). Distinguir os agentes causais é um passo crítico para manejá-los eficazmente. Em levantamento recente efetuado em cinco áreas de cultivo de arroz no Vale do Paraíba, Brasil, e nos Llanos na Colômbia, R. oryzae-sativae, o patógeno da mancha agregada da bainha, foi a espécie predominante em ambos os países. Neste estudo, nosso principal objetivo foi determinar a estrutura genética das populações de R. oryzae- sativae do arroz no agroecossistema da região do Vale do Paraíba e nos Llanos Colombianos. Inferiu-se sobre o fluxo gênico entre populações do patógeno, dentro e entre os países, e sobre o modo reprodutivo predominante. Nosso segundo objetivo foi determinar o potencial de duas populações brasileiras de R. oryzae-sativae em adaptar-se a espécies forrageiras do gênero Urochloa. Uma vez que essas espécies de forrageiras são cultivadas em áreas adjacentes ou em rotação com arroz, podem estar exercendo elevada pressão de seleção sobre as populações de R. oryzae- sativae. Análises da estrutura genética de populações foram baseadas na genotipagem de isolados de quatro populações do patógeno usando cinco marcadores microssatélites. Populações próximas e distantes apresentaram indícios de fluxo gênico. Evidências de reprodução sexuada nas populações do patógeno e a baixa fração clonal, indicaram a predominância de um sistema reprodutivo recombinante. É provável que basidiósporos desempenhem papel mais importante no ciclo da doença do que se supunha anteriormente. Isolados das duas populações brasileiras de R. oryzae-sativae foram patogênicos e apresentaram variação na agressividade à Urochloa spp., porém com baixos índices de herdabilidade,...
Keywords: Arroz - Doenças e pragas; Genetica de populações; Gramínea - Braquiaria; Rice -- Diseases and pests